Development finance, blended finance and insurance. Issue 1 (30th June 2020) - Jung, Hongjoo
Abstract : Purpose: This research aims to review literature on development finance and its challenge and to examine blended learning and insurance as a catalysts of development finance. In particular, this paper provides new insights and practical examples of blended finance and insurance. Design/methodology/approach: This research basically relies on literature review and case study to show the value of the emerging methods of blended learning in development finance and insurance system. Findings: Basic finding in this paper includes new insight of blended finance and insurance as a partnership between public and private sector, which offers new arena for academic research and practice. Originality/value: As the research relies on literature review and authors' insight, originality may not be valued so much, but if may be introducing or creating new ideas or thinking about development finance or international development cooperation where relevant data or experience is still lacking.